2020
DOI: 10.14202/vetworld.2020.2006-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre and postpartum alpha-tocopherol supplementation on milk yield, milk quality, and udder health of Jersey crossbred cows at tropical lower Gangetic region

Abstract: Background and Aim: Alpha-tocopherol supplementation influences milk yield, milk quality, and udder health of dairy cows, which needs to be investigated for Jersey crossbred cows at hot-humid climate. Therefore, the present study was framed with an objective to study the effect of pre and postpartum Alpha-tocopherol supplementation on milk yield, milk quality, and udder health status of Jersey crossbred cows at tropical climate. Materials and Methods: For this study, 19 similar parity, body condition score, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Developed countries also suffer high financial losses which ultimately leads to culling, poor milk production, compromised udder health status and reduced reproductive performances of farm animals (Laxmi, 2016). Besides leading to heavy losses in milk production, the SCM animals may remain potent source of infection to other animals in the herd (Swami et al, 2017;Singh et al, 2020e;Garai et al, 2021, Singh et al, 2021a and causing poor udder health maintenance throughout lactation.…”
Section: Impact Of Scm/ Udder Healthmentioning
confidence: 99%
“…Developed countries also suffer high financial losses which ultimately leads to culling, poor milk production, compromised udder health status and reduced reproductive performances of farm animals (Laxmi, 2016). Besides leading to heavy losses in milk production, the SCM animals may remain potent source of infection to other animals in the herd (Swami et al, 2017;Singh et al, 2020e;Garai et al, 2021, Singh et al, 2021a and causing poor udder health maintenance throughout lactation.…”
Section: Impact Of Scm/ Udder Healthmentioning
confidence: 99%
“…"Vitamin E includes a group of tocopherols and tocotrienols, among them, α-tocopherol has greater biological activity. Due to the potent antioxidant properties of tocopherols, the impact of α-tocopherol in the prevention of chronic diseases believed to be associated with oxidative stress has often been studied and beneficial effects have been observed" [62,11,63,12]. Supplementation of vitamin E along with selenium (500 IU Vitamin E + 0.3mg selenium per kg DM) alleviated heat stress in dairy cows.…”
Section: Vitamin Ementioning
confidence: 99%
“…As the science progressed, advancements in improved genetics, nutrition and management practices in dairy animals have been enhanced [1][2][3]. The prime priority of every dairy farmer or be it any dairy industry is higher milk quality and quantity [4][5][6]. However, SM has emerged as one of the major challenging diseases among other diseases in dairy animals [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis may be understood as inflammation of the mammary gland mainly due to different bacterial strains [1,4,5,12]. However, some studies also reported that SM may be caused by yeasts.…”
Section: Introductionmentioning
confidence: 99%